(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
Maintenance of cold chain points are vital for preserving potency of vaccines for immunization of children and thereby averting vaccine preventable diseases in the community. Cold chain handlers should have sufficient knowledge and skills related to cold chain equipment handling and immunization practices. The present study aims to evaluate maintenance of cold chain facilities at primary health care centers (PHCs), related logistics and observation of Mamta Day (Immunization Day). The observations include knowledge and practice of health workers about immunization activities, their communication skills, training status etc. Methods: There are total 31 Primary Health Centers in Jamnagar district, out of which, we decided to include 50% (15) of primary health centers and observed their cold chain, and Immunization day at a subcentre or Anganwadi centre of the selected PHC to assess the quality of immunization services. We included equal number of cold chain points from each block of the district to make it representative of entire district. Results: Average population served by a cold chain point is 21985. Vaccine related logistics like cold boxes, vaccine carriers etc. were adequate in all facilities. All cold chain equipments were placed as per standard guidelines. The posts of medical officers and pharmacists were vacant in almost one fourth of cold chain points and they were run on deputation from other facilities. The knowledge and skills of health workers related to immunization practices were found to be satisfactory. Conclusion: We observed that routine immunization program was implementing in the district satisfactorily. The posts of medical officers and pharmacists need to be filled up at the earliest for smooth functioning of immunization program in primary health centres.